Pola Komunikasi; Interaksi Guru dan Murid dalam Pembelajaran Berbasis Budaya - Weinona Putri Aisya; Luthfi Awwalia (Journal of Social, Culture, and Language, 2023)
The interaction between teachers and students during the learning process creates a certain communication pattern. There are five communication patterns that exist in the classroom, including teacher-student, teacher-student-teacher, teacher-student-student, teacher-student-student-teacher-student, and circular. The research aims to uncover the communication patterns that occur in English language learning with materials related to local Madura culture at Madrasah Aliyah Bangkalan, Madura. Using a qualitative descriptive method by observing the learning process inside the classroom and interviewing teacher and students. The results showed that the communication pattern that emerges was teacher-student-student, teacher-student-student-teacher-student. This was the result of collaboration between the teaching methods applied by the teacher and the material that was equally interesting for the students. Furthermore, the use of local culture should not be overlooked in language learning, especially in local culture. The teacher's ability to manage the class is also the key to positive interaction and increased student interest in learning. Keywords: pattern, communication, culture, learning